2022
DOI: 10.1037/ser0000500
|View full text |Cite
|
Sign up to set email alerts
|

Preferences regarding therapists’ history of personal therapy or suicidal ideation: A comparison of undergraduates and mental healthcare providers.

Abstract: A majority of mental health care providers seek personal therapy (i.e., are prosumers), and many providers experience suicidal ideation. Although mental health care providers may have more awareness of mental health than undergraduates, stigma is prevalent across both mental health care professionals and within universities. Furthermore, suicidality is a particularly stigmatized aspect of mental health. Stigma may affect a client’s willingness to work with therapists who are prosumers. Although client preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The scarce research available on this topic has indicated that both providers and clients generally have positive reactions to the use of personal therapy (Elkins et al, 2017; Orlinsky et al, 2011); however, preferences differ depending on the reason for seeking treatment and the specific type of lived experience (Elkins et al, 2017). The present study serves as a replication and extension of prior work (particularly Bulla et al, 2022) and examines potential client preferences for a therapist who has sought personal therapy, experienced suicidal ideation, or made a suicide attempt in a sample of community members.…”
Section: Views Of Providers’ Personal Therapy Usagementioning
confidence: 88%
See 4 more Smart Citations
“…The scarce research available on this topic has indicated that both providers and clients generally have positive reactions to the use of personal therapy (Elkins et al, 2017; Orlinsky et al, 2011); however, preferences differ depending on the reason for seeking treatment and the specific type of lived experience (Elkins et al, 2017). The present study serves as a replication and extension of prior work (particularly Bulla et al, 2022) and examines potential client preferences for a therapist who has sought personal therapy, experienced suicidal ideation, or made a suicide attempt in a sample of community members.…”
Section: Views Of Providers’ Personal Therapy Usagementioning
confidence: 88%
“…Despite these limitations, the present study has several unique strengths including the use of a delay discounting paradigm to assess treatment preferences and the unique consideration of participants’ experiences with suicidal thoughts and behaviors. The study was designed as a replication and extension of previous work elucidating lesser preferences for providers with a history of suicidal ideation (Bulla et al, 2022). Consistently, our findings demonstrate that a nontreatment seeking community sample reported a lesser preference for providers who had a history of suicidal ideation and attempts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations